Awareness of third-hand smoke: A cross-sectional study among medical students at Qassim University - Eman Abdullah Alotaibi; Mohammed Khalid Alrasheed; Ibrahim Helal Almutairi; Khaled Mounir Almoutairi; Abdulrahman Abdullah Aladdad; Abdulaziz Abdulmohsen Alharbi; Sufyan Ahmad Albaibi; Abdulaziz Hamad Alsadun; Muffarah Hamid Alharthi (Journal of Family Medicine and Primary Care)
Introduction: Third-hand smoke refers to pollutants that linger on surfaces and in the environment well after smoking has stopped. These substances can be inhaled, ingested, or absorbed through the skin. These persistent toxins, which settle on walls, furniture, and clothing, are linked to serious health issues such as asthma, reproductive system disorders, postpartum depression, and sleep disturbances in children. Methods: The study employed a cross-sectional research design to assess the perceptions of Qassim University medical students regarding third-hand smoke. The study included 377 participants, with data collected through an electronic, self-administered Beliefs About Third-Hand Smoke (BATHS) questionnaire. The data analysis was conducted using SPSS Version 27. Results: The results show that majority of respondents believe that lingering air can harm the health of infants and children (78.6%). Almost two-thirds (74.6%) also believe that these particles are absorbed into furniture and walls, while a majority (62%) think that the particles can persist in a room for several weeks. Females demonstrated slightly higher median overall belief scores (33) compared with males (32), with a P value of 0.09. Smokers had a lower median persistent belief score (13) compared with nonsmokers (15); this difference was statistically significant with a P value of 0.041, suggesting that smokers may be less convinced about the persistence of smoke particles. Conclusion: The study found strong awareness among medical students about the persistence and health risks of third-hand smoke. The majority of the students understood that standard ventilation cannot fully eliminate smoke particles, which can linger on surfaces and pose health risks. However, smokers were less concerned about this persistence, and perceptions varied by gender. The findings suggest a need for targeted educational programs to improve understanding of third-hand smoke among both medical students and the general population.